Expeditions to Knowledge (2011)
Discovering, planning, developing and concluding are the phases of Expeditions to Knowledge. This year, 15 topics were addressed in this stage, including environment and biodiversity; energy and natural resources, physics and universe, communication and technology, transportation and housing, philosophy, history and social conflicts, music, art and culture, among others.